Propafenone for supraventricular arrhythmias in septic shock-Comparison to amiodarone and metoprolol - Balik, M; Kolnikova, I; Maly, M; Waldauf, P; Tavazzi, G; Kristof, J (Journal of critical care, 2017)
PURPOSE: The occurence of supraventricular arrhythmias associate with an unfavourable prognosis in septic shock. Propafenone could be a feasible antiarrhythmic. MATERIALS AND METHODS: Patients collected over a period of 24months were divided into the three groups based on antiarrhythmic: Group1(amiodarone), Group2(propafenone), Group3(metoprolol). Type of arrhythmia, cardioversion rates, demographic, haemodynamic, laboratory parameters were recorded in the first 24h. The outcome data were compared between the groups. RESULTS: 234 patients (99.1% ventilated) were included, the prevailing arrhythmia was acute onset atrial fibrillation (AF,69.7%). Except for the dosage of noradrenaline (0.35(0.14-0.78) in Group1(n=142)vs 0.25(0.10-0.50),p<0.01 in Group2(n=78)vs 0.14(0.07-0.25)μg/kg·min,p<0.05 in Group3(n=14)) the ejection fraction of left ventricle, rates of renal replacement therapy, arterial lactate and procalcitonin levels were not different between the groups. The cardioversion rate in Group1(74%) was lower than in Group2(89%) and Group3(92%). ICU and 28-day mortalities of Group1 were not significantly higher than in Group2 and Group3. Multivariate analysis demonstrated higher 12-month mortality in Group1 than in Group2 (HR1.58(1.04;2.38),p=0.03). CONCLUSIONS: Propafenone demonstrated a higher cardioversion rate than amiodarone with a similar impact on the outcome. Patients remaining in acute onset arrhythmia did not demonstrate significantly higher ICU, 28-day and 12-month mortalities compared to those successfully cardioverted or to those having chronic AF.
Keywords: propafenon; Betablockers; Septic shock; Propafenone; Humans; elektrická defibrilace; lidé středního věku; Amiodarone; Female; Aged; Critical Care; Tachycardia, Supraventricular; výsledek terapie; Supraventricular arrhythmia; senioři; péče o pacienty v kritickém stavu; lidé; metoprolol; septický šok; supraventrikulární tachykardie; Electric Countershock; Shock, Septic; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Treatment Outcome; antiarytmika; Anti-Arrhythmia Agents; retrospektivní studie; mužské pohlaví; Metoprolol; amiodaron